Absolute and multiplex quantification of antibodies in serum using PSAQ™ standards and LC-MS/MS. (May 2015) - Lebert, Dorothee; Picard, Guillaume; Beau-Larvor, Charlotte; Troncy, Lysiane; Lacheny, Christine; Maynadier, Bernadette; Low, Walter; Mouz, Nicolas; Brun, Virginie; Klinguer-Hamour, Christine; Jaquinod, Michel; Beck, Alain
Background : In preclinical studies, monoclonal antibodies (mAbs) are traditionally assayed by ligand-binding-assays. Recently, quantitative liquid chromatography mass spectrometry (MS)-based assays have emerged which circumvent a number of challenges. These assays may also be multiplex, making them potentially compatible with pharmacokinetic assays for combined antibody therapies.Materials & methods : We combined a quantitative MS-based approach with the protein standard for absolute quantification (PSAQ™) strategy to simultaneously quantify three mAb variants presenting minor sequence differences. Stable isotopically labeled mAbs were produced and used as quantification standards. Titration curves were performed to assess the analytical performances of the method. LC-MS/MS and ELISA data were cross-compared.Results : The approach presented provides similar accuracy and precision than ELISA, while being multiplex and faster to develop. It has applications at all stages of the pharmaceutical development.